Thermoacidophilic Alicyclobacillus Superoxide Dismutase: Good Candidate as Additives in Food and Medicine - Dong, Xueqian; Wang, Wei; Li, Shannan; Han, Hongyu; Lv, Peiwen; Yang, Chunyu (Frontiers in Microbiology, 2021)
Thermoacidophilic Alicyclobacillus strains attract great interests as a resource of thermostable or acidic enzymes. A putative gene encoding superoxide dismutase (AaSOD) was identified in a thermoacidophilic Alicyclobacillus strain. In the growth media with manganese or iron enrichment, the activity of expressed AaSOD showed great preference to manganese, with a 16-fold activity observed in the Mn2+-enriched medium. In addition, the purified AaSOD can be reconstituted exclusively with either Fe2+ or Mn2+, with its Mn-bound protein showing 25-fold activity than that of Fe-bound form. The optimal temperature of AaSOD was 35 °C and was highly stable at high temperature. Of particular interest, the enzyme is found to be very stable across a wide pH range spanning from 2.0 to 10.0, which confers its robust stability in the acidic stomach environment and implies striking potentials as food and medicine additives.